A new oleanane type pentacyclic triterpenoid saponin from the husks of xanthoceras sorbifolium bunge and its neuroprotection on PC12 cells injury induced by Aβ25-35. Issue 22 (16th November 2020) - Ding, Kewen; Guo, Sirui; Rong, Weiwei; Li, Qing; Liu, Ran; Xu, Huarong; Yin, Yidi; Bi, Kaishun
Abstract: A new triterpenoid saponin (1 ), 3- O -[ β -D-glucopyranosyl(1→6)]-(2′ -angeloyl)- β -D-glucopyranosyl-28- O - β -D-glucopyranosyl(1→6)[ α -L-rhamnopyranosyl(1→2)- β -D-glucopyranosyl]-21- O -acetyl-16-deoxybarringtogenol C, together with four known saponins (2 ∼ 5 ) were isolated from the husks of Xanthoceras sorbifolium Bunge . Their structures were characterized by HR-ESI-MS, 1D-NMR, 2D-NMR spectra and chemical methods. Compound 1 exhibited excellent neuroprotection on PC12 cells injury induced by Aβ25-35 at the doses of 150 μmol/L and 200 μmol/L. The cell viabilities were (76.18 ± 2.09) % and (76.02 ± 3.20) %, respectively.